2018
DOI: 10.5812/ans.67577
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Word Retrieval Therapy in Primary Progressive Aphasia: A Single-Case Study

Abstract: Background: Anomia is a common symptom that can be detrimental to the everyday communication of patients with primary progressive aphasia (PPA). Studies on the anomia treatment in PPA demonstrate that re-learning is possible, but the maintenance and generalization of improvements are limited. The treatment of word retrieval in PPA has typically centered on the retrieval of single lexical items. Little is known about the effects of word-finding treatments in discourse tasks on lexical retrieval. Objectives: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Specifically, all studies have reported significant immediate gains in oral and/or written naming for trained items regardless of the grammatical class treated. However, most studies, except a few [66,77,79,80,83,84], have failed to show larger generalization effects of a particular lexical retrieval treatment technique for untrained items when applied to a specific variant of PPA. Studies that examined this aspect have also reported effects on language tasks such as syntactic generation tasks [76] and discourse measures [79] after lexical retrieval cueing hierarchy treatment in nf/avPPA and svPPA subjects, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, all studies have reported significant immediate gains in oral and/or written naming for trained items regardless of the grammatical class treated. However, most studies, except a few [66,77,79,80,83,84], have failed to show larger generalization effects of a particular lexical retrieval treatment technique for untrained items when applied to a specific variant of PPA. Studies that examined this aspect have also reported effects on language tasks such as syntactic generation tasks [76] and discourse measures [79] after lexical retrieval cueing hierarchy treatment in nf/avPPA and svPPA subjects, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As already described, naming impairment in PPA may reflect breakdown at one or more stages of the naming process [33][34][35]. In line with these considerations, several studies have investigated the effectiveness of naming treatments, including semantic, lexical-phonological and lexical-orthographic interventions and/or the combination of them, in patients with progressive wordfinding difficulties [21,25,60], but only a few studies have compared the effects of different approaches in the same PPA-subtype patients [65][66][67][68][69][70][71][72][73][74].…”
Section: Naming Treatment In Ppamentioning
confidence: 97%
See 3 more Smart Citations